Navigating Homeopathy: Patient Expectations vs. Physician Realities - Brij, Kishan Kumar, Megha; Devi, Haobam Vidyalaxmi; Gautam, Abhishek (Indian Journal of Integrative Medicine, 2025)
Homoeopathy is a holistic medical system that uses highly diluted substances to stimulate the body’s self-healing mechanisms. While many patients report significant improvements, others experience dissatisfaction due to slow progress, initial aggravation of symptoms, or unmet expectations. Similarly, homoeopathic physicians encounter challenges related to patient non-compliance, unrealistic demands, and scepticism from the broader medical community. This article evaluates the factors contributing to patient and physician dissatisfaction through case analyses, addressing challenges, and proposing practical solutions to bridge the gap. Homoeopathy can further establish its credibility as a reliable medical practice by enhancing patient education, managing expectations, and improving compliance.